Avaliação de aspectos cefalométricos, tomográficos e polissonográficos em indivíduos com picnodisostose - Couto, José Luciano Pimenta (2015)
Introduction: The aim of the presente study was to evaluate the airway space in pacients with pycnodysostosis (PKND), associating these findings with the results obtained from polysomnographies. Methods: Nine patients with PKND were selected to participate in the present study. Lateral cephalometric radiographs and computed tomographies of the face were obtained. Cephalometric (UNIFESP-sono) and tomographic parameters were adopted, in which the total volume of the upper airway and the dimensions from five transverse pharyngeal areas were evaluated. Tomographic and cephalometric images from 9 healthy, non-syndromic individuals, pared by age and gender were used as controls. Results: Patients with PKND presented great craniofacial involvement, with a retrognathic maxillary and mandibular pattern of malocclusion, a tendency towards vertical growth and a mandibular clockwise rotation, associated with an inferior displacement of the hyoid bone, compared to the control (P<0,05). In addition, a statistically significant reduction in the upper airway volume and the five transverse pharyngeal sections was observed. The polysomnography revealed a 55.6% prevalence of obstructive sleep apnea syndrome (OSAS) among PKND patients. Conclusions: Individuals with PKND express a series of skeletal craniofacial anomalies correlated with a narrowing of the airway, and these factors are related with the diagnosis of OSAS.